PENENTUAN STATUS KUALITAS AIR PERAIRAN PANTAI TANJUNG BAYANG KOTA MAKASSAR MENGGUNAKAN INDEKS PENCEMARAN: Determination of Water Quality Status in the Coastal Waters of Tanjung Bayang, Makassar City, Using the Pollution Index) - Kartini J; Aminuddin Aminuddin; Nudia Tuljannah; Afifah Nur Fadhilah (JURNAL AKUAKULTUR, TEKNOLOGI DAN MANAJEMEN PERIKANAN TANGKAP, ILMU KELAUTAN, 2026)
The coastal waters of Tanjung Bayang Beach, Makassar City, are utilized for various activities, including fisheries, tourism, and residential settlements. The intensity of these activities has the potential to degrade water quality due to the input of pollutants, making an assessment of water quality status essential for sustainable coastal management. This study aimed to determine the water quality status of the Tanjung Bayang coastal waters using the Pollution Index (PI) method. Water samples were collected from three sampling stations, namely the Jeneberang River Estuary, Tanjung Bayang Beach, and Anging Mammiri Beach (Blue Beach), during both high and low tide conditions. Water quality status was evaluated using the Pollution Index method in accordance with the Decree of the Minister of Environment No. 115 of 2003, with reference to the marine water quality standards stipulated in the Decree of the Minister of Environment No. 51 of 2004. The results showed that Pollution Index values ranged from 0.71 to 1.68 during low tide and from 0.718 to 1.868 during high tide. The water quality status at all sampling stations ranged from good condition to lightly polluted. During low tide, the lightly polluted category was identified at several sampling points in the Jeneberang River Estuary and Tanjung Bayang Beach, while similar conditions were also observed at several points during high tide. Overall, the level of pollution tended to be higher during high tide than during low tide, indicating the need for regular water quality monitoring to support sustainable coastal water management.